The SMRT Coregulator Enhances Growth of Estrogen Receptor-α-Positive Breast Cancer Cells by Promotion of Cell Cycle Progression and Inhibition of Apoptosis - Blackmore, Julia K. (Endocrine Society, 2014)
The SMRT coregulator functions as a dual coactivator and corepressor for estrogen receptor-α (ERα) in a gene-specific manner, and in several studies its elevated expression correlates with poor outcome for breast cancer patients. A specific role of SMRT in breast cancer progression has not been elucidated, but SMRT knock-down limits estradiol-dependent growth of MCF-7 breast cancer cells. In this study, small-interfering RNA (siRNA) and short-hairpin RNA (shRNA) approaches were used to determine the effects of SMRT depletion on growth of ERα-positive MCF-7 and ZR-75–1 breast cancer cells, as well as the ERα-negative MDA-MB-231 breast cancer line. Depletion of SMRT inhibited growth of ERα-positive cells grown in monolayer but had no effect on growth of the ERα-negative cells. Reduced SMRT levels also negatively impacted the anchorage-independent growth of MCF-7 cells as assessed by soft agar colony formation assays. The observed growth inhibitions were due to a loss of estradiol-induced progression through the G1/S transition of the cell cycle and increased apoptosis in SMRT-depleted compared with control cells. Gene expression analyses indicated that SMRT inhibits apoptosis by a coordinated regulation of genes involved in apoptosis. Functioning as a dual coactivator for anti-apoptotic genes and corepressor for pro-apoptotic genes, SMRT can limit apoptosis. Together these data indicate that SMRT promotes breast cancer progression through multiple pathways leading to increased proliferation and decreased apoptosis.